Testing for weak exogeneity and superexogeneity in money demand for some Caribbean countries - Ghartey, Edward ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Examines the exogeneity conditions of money demand in Barbados and Jamaica.